New Approaches in Assistive Technologies Applied to Engineering Education - Artifice, Andreia (2020)
The authors acknowledge the European Commission for its support and partial funding and the partners of the research project from ERASMUS+: Higher Education— International Capacity Building—ACACIA—Project reference number—561754-EPP-1-2015-1-CO-EPKA2-CBHE-JP, (http://acacia.digital).